2017
DOI: 10.1093/ndt/gfx257
|View full text |Cite
|
Sign up to set email alerts
|

Does Kidney Donor Risk Index implementation lead to the transplantation of more and higher-quality donor kidneys?

Abstract: BackgroundThe Kidney Donor Risk Index (KDRI) is a quantitative evaluation of the quality of donor organs and is implemented in the US allocation system. This single-centre study investigates whether the implementation of the KDRI in our decision-making process to accept or decline an offered deceased donor kidney, increases our acceptance rate.MethodsFrom April 2015 until December 2016, we prospectively calculated the KDRI for all deceased donor kidney offers allocated by Eurotransplant to our centre. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
0
15
0
2
Order By: Relevance
“…The Kidney Donor Risk Index (KDRI)/Kidney Donor Profile Index (KDPI), derived from donor characteristics, was developed in the USA in an effort to devise an objective means of assessing donor organ suitability based on predicted graft survival [1]. The association of the KDRI with graft failure is founded on Cox proportional hazards models of 70 000 donors in the USA from 1995 to 2005 [2], and use of this score has influenced kidney organ allocation in the USA [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…The Kidney Donor Risk Index (KDRI)/Kidney Donor Profile Index (KDPI), derived from donor characteristics, was developed in the USA in an effort to devise an objective means of assessing donor organ suitability based on predicted graft survival [1]. The association of the KDRI with graft failure is founded on Cox proportional hazards models of 70 000 donors in the USA from 1995 to 2005 [2], and use of this score has influenced kidney organ allocation in the USA [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…At least in the USA, KDPI has a potential to influence the clinical decision on whether to accept or discard a donor kidney, but there is no uniform view on its robustness since the graft outcomes depend also on other donor factors and recipient characteristics. Up to now, there have been a lot of debates about KDPI, and while some authors found its use increased the acceptance of donors and lead to rise in transplantation rate [7] and robustly predicted kidney graft survival [8], others doubted about its generalizability to non-US [9] and non-adult populations [10, 11], and caution about formal KDPI use as a criterion of organ discard [12, 13]. KDPI > 85% is thought to be equivalent to an extended criteria donor (ECD) kidney (while the KDPI is based on 10 parameters, the historical ECD definition is based on only 4 parameters), but almost twice less donors were classified as ECD according to KDPI> 85% in comparison with the historical ECD definition, and thus were accepted for transplantation [12].…”
Section: Discussionmentioning
confidence: 99%
“…Menos de randômica, de modo que ao se analisar separadamente cada uma delas o resultado encontrado não sofreu interferência pela outra. Além disso, mostra que o processo de seleção dos enxertos renais no serviço sede do estudo não está de acordo com o preconizado pela Rede de Aquisição e Transplante de Órgãos dos Estados Unidos (Organ Procurement and Transplantation Network -OPTN) (8)(9) e por Philipse et al (1) . Tais fontes priorizam a existência de uma correlação direta entre os valores de KDPI dos enxertos e de EPTS dos receptores.…”
Section: Categoriaunclassified
“…A menor mortalidade e a maior qualidade de vida proporcionadas pelo transplante renal, em comparação com a terapia dialítica, configuram este como o tratamento de escolha para a doença renal em fase terminal (1)(2)(3) . A escassez de rins disponíveis, entretanto, frequentemente leva à utilização de enxertos de menor qualidade, que, em tese, deveriam ser destinados a pacientes com menor expectativa de vida (1). Desse modo, foram desenvolvidas ferramentas para predizer o prognóstico pós-transplante dos rins doados e dos receptores a fim de orientar essa decisão.…”
Section: Introductionunclassified